Acontrastive analysis of euphemisms in the fourth and fifth books of the novel series “harry potter” and their Vietnamese translational equivalents - Hồ Diệu Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The thesis was carried out with the aim of identifying the euphemistic expressions in the fourth and fifth books of the “Harry Potter” series and their Vietnamese translational equivalents and analyzing the translation strategies used when translating these euphemistic expressions into Vietnamese. The study’s statistics were gathered from two volumes of the novel series namely “Harry Potter and the Goblet of Fire” and “Harry Potter and the Order of the Phoenix,” as well as their Vietnamese translational versions “Harry Potter và Chiếc cốc lửa” and “Harry Potter và Hội Phượng hoàng”. Both qualitative and quantitative analyses were performed on 328 euphemistic expressions (164 in English, 164 in Vietnamese). The strategies of translating English euphemisms into Vietnamese and the frequency of occurrence of the specified translation strategies were discovered and examined using the theoretical foundation displayed in chapter 2. The study’s findings indicated the essential role of translators in the translation process and suggested that translators should carefully select the appropriate conveyance for each context so that the translation would make sense and could deliver the message to the readers. The recommended translation strategies were used when translating euphemisms from the fourth and fifth books of the “Harry Potter” series into Vietnamese are: Translating a euphemism by using a direct word, translating a euphemism by using a more general word, translating a euphemism by using a more neutral/ less expressive word, translating a euphemism by using a loan word or loan word plus explanation, translating a euphemism by paraphrase using a related word, and translating a euphemism by paraphrase using an unrelated word. The results of this thesis were expected to be useful for further research on euphemisms and euphemism translation and contribute to reli